STRATEGI GURU AGAMA HINDU DALAM PENINGKATAN ETIKA HINDU DI SMPN 14 MATARAM - Ni Ketut Ayu Sugiartini; I Putu Ayu Paramita Dewi; Ida Bagus Kade Yoga Pramana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to explore the strategies employed by Hindu religious teachers in enhancing Hindu ethics among students. Utilizing a qualitative research approach, data were collected through interviews and observations in various educational settings. The findings reveal that effective strategies include the integration of ethical teachings into daily lessons, the use of interactive teaching methods, and the involvement of the community in ethical education. The study concludes that these strategies significantly contribute to the improvement of students' understanding and practice of Hindu ethics, fostering a more profound moral development in the educational environment.